Practical method of the evaluation and selection procedure of a logistics provider in a technological environment provided by digitalization - Nagy, Gábor; Bányai, Ágota; Illés, Béla (Advanced Logistic Systems - Theory and Practice, 2023)
The purpose of the study is to present the possibility of evaluating and selecting a logistics service provider from a practical point of view in the digitalization environment of the fourth industrial revolution. We will present a possible procedure that makes it possible to use large amounts of data in the evaluation of a service provider. As a result of the task, the organization responsible for the decision receives exact information about the performance of the service providers present in the competitive market according to its own needs, in this way each company can decide and choose the ideal/optimal service provider according to the conditions it considers important.